The effects of pre-slaughter selection of reindeer bulls (Rangifer tarandus tarandus L.) on technological and sensory meat quality, blood metabolites and abomasal lesions - Wiklund, E.; Malmfors, G.; Lundström, K. (Rangifer, 1997)
Thirty reindeer bulls (age 1 1/2 years) were subjected to different pre-slaughter treatments to study the effects on ultimate pH values, muscle glycogen content, blood metabolites and abomasal lesions. Gathering and herding into a grazing corral were followed by various selection procedures. Before starting these, a control group of 10 reindeer were captured by lasso and slaughtered outside the grazing corral. Ten reindeer were then selected by hand from a small group of animals (100-150 head) in a small selection corral. Another 10 reindeer were selected from a large herd of about 1000-2000 animals, by the traditional technique of using a lasso. During a 6-hour selection, animals were captured and slaughtered after 1.5 hours (n = 2), 3-5 hours (n = 2), 5 hours (n = 3) and 6 hours (n=3) respectively. The results showed the technique of using a lasso to be stressful and glycogen-depleting, as the two lasso captured groups (the control group and the reindeer exposed to the protracted lasso selection) had the highest ultimate pH values and lowest muscle glycogen values measured. By contrast, the selection procedure where reindeer were captured by hand, was not found to be detrimental to glycogen content and ultimate pH values. Nevertheless, both selection techniques expose the reindeer to acute stress during the capture and manual restraint, which in the present study was reflected in high plasma Cortisol values in all treatment groups. The frequency of abomasal lesions was highest in the group of reindeer subjected to the prolonged selection procedure. No connection between technological and sensory meat quality was found in this study. The technique of selecting animals by hand ought to be further developed so that existing practical problems can be solved. The technique could then be recommended for wider use.